A case of recurrent Ludwig’s angina - Raj, Merwin Paul Remson Paul; Lohith Kumar, Manoj Kumar; Hariharan, Anand Kesavan; Krishnamoorthy, Srinivasan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
In this paper, we describe the case of a 45-year-old male who presented with recurrent swelling of the submandibular region. The last episode of the swelling was triggered post tooth extraction. There were associated features like increased temperature and leukocytosis. The patient was started on IV antibiotics and analgesics and with incision and drainage the patient improved with no sequelae.